2009
DOI: 10.1136/emj.2008.057695
|View full text |Cite
|
Sign up to set email alerts
|

Packers, pushers and stuffers--managing patients with concealed drugs in UK emergency departments: a clinical and medicolegal review

Abstract: Body packing, pushing and stuffing are methods by which illicit drugs may be carried within the human body. Patients involved in these practices may present UK emergency departments with complex medical, legal and ethical considerations. This review article examines not only the evidence behind the clinical management of these patients, but also the legal powers afforded to the authorities to authorise the use of intimate searches and diagnostic imaging for forensic purposes. Serious complications from conceal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(108 citation statements)
references
References 26 publications
2
104
1
1
Order By: Relevance
“…No significant change for NPV could be observed, as a negative read with high confidence was only given 4 times in total. The sensitivity of a typical X-ray in diagnosing BP has been reported to ranging from 47% -95% [21] [23], the sensitivity of CT has been reported to be close to 100% [3] [24]. The sensitivity of CT scout view in our human collective of mostly body stuffers was 73% with an especially high PPV, consistent with the higher sensitivity of CT scout view when compared to X-ray as reported in an animal model [12] or for body packing with packets in the upper and mid GI [17].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…No significant change for NPV could be observed, as a negative read with high confidence was only given 4 times in total. The sensitivity of a typical X-ray in diagnosing BP has been reported to ranging from 47% -95% [21] [23], the sensitivity of CT has been reported to be close to 100% [3] [24]. The sensitivity of CT scout view in our human collective of mostly body stuffers was 73% with an especially high PPV, consistent with the higher sensitivity of CT scout view when compared to X-ray as reported in an animal model [12] or for body packing with packets in the upper and mid GI [17].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Body packers, also known as swallowers, internal carriers, couriers or mules, ingest wrapped packets (pellets) containing illicit drugs for purpose of smuggling across borders, while body pushers, with same purpose insert into rectum/vagina. A body stuffer, also known as mini-packer, conversely without smuggling intention ingests poorly wrapped drugs to conceal its presence from custom authorities to avoid arrest or detention (Booker et al, 2009). Body packers/pushers usually smuggle cocaine, less commonly heroin and rarely amphetamine, ecstasy (3,4 -MDMP), marijuana and hashish (Traub et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a few case reports and retrospective observational studies are reported but smuggling of drugs has evolved both in methods of trafficking with better concealment (e.g., using automatic crafted packing system leading to minimal chance of rupture/leak or use of aluminum foil, plastic food wrap, carbon paper to alter radio density limiting detection by authorities) and methods of detection by increasing security in airport, marine or border area (Pidoto et al, 2002). Packet failure may occur in country of origin, during flight or at their destination and may present to health care providers as Body packer syndrome (Booker et al, 2009) . Drug trafficking is a global illicit trade, continuously monitored by United Nations Office on Drugs and Crime (www.unodc.org) and many countries are signatory to international Conventions (e.g., Single Convention on Narcotic Drugs, 1961, Convention on Psychotropic Substances, 1971 and the UN Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances, 1988, http://cbn.nic.in); however, each country's legal policy controls it independently.…”
Section: Introductionmentioning
confidence: 99%
“…Body stuffers, including traffickers and users, ingest intentionally small amounts of loosely wrapped drug pellets (typically initially hidden in the mouth), usually immediately before an unexpected encounter with law enforcement. [5][6][7][8][9][10] The generally accepted radiological examination is a plain abdominal radiograph in the supine projection. [4][5][6] This technique is widely available at a low cost and is a simple method of detecting drug-filled packets within the alimentary tract.…”
mentioning
confidence: 99%